2-6p=-8-5p

Simple and best practice solution for 2-6p=-8-5p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2-6p=-8-5p equation:


Simplifying
2 + -6p = -8 + -5p

Solving
2 + -6p = -8 + -5p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '5p' to each side of the equation.
2 + -6p + 5p = -8 + -5p + 5p

Combine like terms: -6p + 5p = -1p
2 + -1p = -8 + -5p + 5p

Combine like terms: -5p + 5p = 0
2 + -1p = -8 + 0
2 + -1p = -8

Add '-2' to each side of the equation.
2 + -2 + -1p = -8 + -2

Combine like terms: 2 + -2 = 0
0 + -1p = -8 + -2
-1p = -8 + -2

Combine like terms: -8 + -2 = -10
-1p = -10

Divide each side by '-1'.
p = 10

Simplifying
p = 10

See similar equations:

| 6+12+(49-30)+5= | | Y=cot^4(7x^2) | | -d^2=13d | | 4p=280 | | x-(6+3x)=28 | | 2/3x11/2 | | X^2-16x+y^2=36 | | Y=8x(tanx) | | 9z-14z=207 | | Y=8x(tanc) | | 6+6-6= | | 10+p=6 | | F(x)=15 | | 101-9y=29 | | 7-4x=4+3x | | Y-60=-17//2(x-20) | | 42-2x=5 | | -2x-2=2x+14 | | 13-6x=7-8x | | 122/75 | | We+14=8(q+7) | | -31+a=-6 | | 5x^2-14+49=0 | | 3(x-1)-4(x-1)=36x+24 | | -8(x/2-y/4)= | | x+squrt(4x)-5=0 | | ln(4x-3)+ln(x+1)= | | -2(4a+3b)= | | -11+y=-31 | | 5+6log^2x=14 | | -1=3(3x-2) | | (3x^2y)(5x^2y^2-6xy+2)= |

Equations solver categories